2009
DOI: 10.1177/1538574409335037
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Roxithromycin for Preventing Progression of Small Abdominal Aortic Aneurysms: Long-Term Results of a Small Clinical Trial

Abstract: Annual 4 week treatment with 300 mg roxithromycin daily may reduce the progression of small AAAs, and later need for surgical repair. However, more robust studies are needed for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…They showed that the expansion rate of AAAs treated with doxycycline was slower than with placebo, but the difference did not reach statistical significance [ 54 ]. Treatment with roxithromycin, a macrolide antibiotic, significantly reduced the AAA expansion rate [ 55 , 56 ]. However, it is not clear whether the effect was due to its anti-microbial or anti-inflammatory activities.…”
Section: Current Statusmentioning
confidence: 99%
“…They showed that the expansion rate of AAAs treated with doxycycline was slower than with placebo, but the difference did not reach statistical significance [ 54 ]. Treatment with roxithromycin, a macrolide antibiotic, significantly reduced the AAA expansion rate [ 55 , 56 ]. However, it is not clear whether the effect was due to its anti-microbial or anti-inflammatory activities.…”
Section: Current Statusmentioning
confidence: 99%
“…13 The second study, also a small RCT, reported a borderline effect of a 4 week treatment with roxithromycin on AAA progression (p ¼ .055). 33 The effect of azithromycin, another member of the macrolide class, was investigated in a larger RCT conducted by Karlsson et al 34 in 2009 (n ¼ 247). This study did not observe a significant difference between the AAA expansion rate in the azithromycin treated patients and controls.…”
Section: Statinsmentioning
confidence: 99%
“…Thus, although the exact role of C. pneumoniae in pathogenesis of aortic aneurysm remains to be clarified, the results of several prospective clinical trials could provide some contribution to this matter. It has been proven, that antibiotics effective against C. pneumoniae -tetracyclines (doxycyclin) and macrolides (roxithromycin, but not azithromycin), may reduce the progression of small aortic aneurysm (Høgh et al, 2009, see also chapter 3.5.2.2). Based on mentioned observations one can expect a direct correlation between the presence of C. pneumoniae and tissue levels of MMPs in aneurismal aortic wall specimens.…”
Section: Chlamydia Pneumoniae and Mmps In Aortic Aneurysmmentioning
confidence: 99%